2015
DOI: 10.1038/nature14859
|View full text |Cite
|
Sign up to set email alerts
|

A cytosolic network suppressing mitochondria-mediated proteostatic stress and cell death

Abstract: Mitochondria are multifunctional organelles whose dysfunction leads to neuromuscular degeneration and ageing. The multi-functionality poses a great challenge for understanding the mechanisms by which mitochondrial dysfunction causes specific pathologies. Among the leading mitochondrial mediators of cell death are energy depletion, free radical production, defect in iron-sulfur cluster biosynthesis, the release of pro-apoptotic and non-cell-autonomous signaling molecules, and altered stress signaling 1–5. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
367
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(377 citation statements)
references
References 33 publications
9
367
0
1
Order By: Relevance
“…These indications are consistent with the observation in yeast that accumulation of mitochondrial proteins in the cytoplasm leads to activation of the unfolded protein response (80). Furthermore, recent studies have reported the presence of polyubiquitinated mitochondrial proteins, suggesting that they are substrates of the ubiquitin proteasome system (81,82) and that in yeast the expression of the proteasome is up-regulated upon cytoplasmic accumulation of mitochondrial proteins (80,83). If mitochondrial import is disrupted and these metastable proteins therefore accumulate in the cytoplasm, the cell responds by clearing them through degradation.…”
Section: Ad-pd Ad-hd Pd-hdsupporting
confidence: 77%
“…These indications are consistent with the observation in yeast that accumulation of mitochondrial proteins in the cytoplasm leads to activation of the unfolded protein response (80). Furthermore, recent studies have reported the presence of polyubiquitinated mitochondrial proteins, suggesting that they are substrates of the ubiquitin proteasome system (81,82) and that in yeast the expression of the proteasome is up-regulated upon cytoplasmic accumulation of mitochondrial proteins (80,83). If mitochondrial import is disrupted and these metastable proteins therefore accumulate in the cytoplasm, the cell responds by clearing them through degradation.…”
Section: Ad-pd Ad-hd Pd-hdsupporting
confidence: 77%
“…Intriguingly, ATFS-1 regulates the expression of skn-1 as part of the UPR mt transcriptional response (9). Finally, accumulation of mitochondrial precursor proteins in the cytosol as a result of impaired mitochondrial import elicits a separate stress-response pathway involving reduced protein translation and increased proteasome activity (12,14). How the UPR mt integrates with these and other cellular stress pathways is therefore an area worthy of further investigation.…”
Section: The Future Of the Upr Mtmentioning
confidence: 99%
“…Under physiological conditions, the MTS directs the localization of ATFS-1 to mitochondria where it is degraded by the protease Lon (7). However, mitochondrial import efficiency is reduced during conditions that perturb mitochondrial function (7,(12)(13)(14), causing ATFS-1 to accumulate in the cytosol and subsequently be imported into the nucleus via its nuclear localization sequence. ATFS-1 regulates a diverse transcriptional response to recover mitochondrial function, including the induction of mitochondrial proteases and chaperones, xenobiotic and ROSdetoxifying genes, and metabolic regulators (7).…”
Section: Caenorhabditis Elegansmentioning
confidence: 99%
“…Whereas numerous studies on the protein transport processes occurring inside mitochondria have been reported, only limited information is available on the early phase of mitochondrial protein biogenesis in the cytosol and its regulation (Harbauer et al, 2014b;Haynes, 2015;Kalderon et al, 2015;Shiota et al, 2015b;Wang and Chen, 2015;Wrobel et al, 2015). Mitochondrial precursor proteins can be bound to cytosolic chaperones and possibly further factors.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…The activity of the mitochondrial protein import machinery is influenced by the energetic state of mitochondria and the folding behavior of proteins and thus will be an important sensor of mitochondrial fitness and quality (Harbauer et al, 2014b). Important topics are the mitochondrial stress response (Ryan and Hoogenraad, 2007), the differential localization of the activating transcription factor associated with stress-1 (ATFS-1) (Nargund et al, 2012;Haynes et al, 2013) and of the mitochondrial kinase PINK1 with important implications for the pathogenesis of familial cases of Parkinson's disease (Lazarou et al, 2012;Yamano and Youle, 2013), and proteostatic responses in the cytosol caused by the accumulation of mistargeted mitochondrial proteins (Haynes, 2015;Wang and Chen, 2015;Wrobel et al, 2015). Research on mitochondrial biogenesis thus spans a broad spectrum from basic studies on molecular mechanisms to cellular regulation, quality control and the involvement of mitochondrial functions in the pathogenesis of human diseases.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%